PENGARUH DIGITAL ENVIROMENT, DYNAMIC MANAGERIAL CAPABILITIES, TRANSFORMATIONAL LEADERSHIP DAN ORGANIZATIONAL CULTURE TERHADAP ORGANIZATIONAL PERFORMANCE - Irbah Ayu Raihani; Dita Oki Berlyanti (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This study aims to analyze the effect of Digital Environment, Dynamic Managerial Capabilities, Transformational Leadership, Organizational Culture on Organizational Performance. The sampling method used is the census of 93 employees of PT. United Tractors Tbk. The data analysis technique in this study uses an instrument test technique using multiple linear regression with the SPSS version 25 application. The results in this study indicate that Digital Environment, Dynamic Managerial Capabilities, Transformational Leadership, Organizational Culture have a positive effect on Organizational Performance. The managerial implication in this research is that the organization is expected to be able to set a shared vision, values, and priorities that are agreed upon by everyone in the organization and that a particular organizational culture must be appropriate under special conditions to increase productivity and efficiency. Keywords: Digital Environment, Dynamic Managerial Capabilities, Transformational Leadership, Organizational Culture, Organizational Performance Penelitian ini bertujuan untuk menganalisis pengaruh Digital Enviroment, Dynamic Managerial Capabilities, Transformational Leadership, Organizational Culture terhadap Organizational Performance. Metode pengambilan sampel yang digunakan adalah sensus yaitu 93 karyawan PT. United Tractors Tbk. Teknik analisis data dalam penelitian ini menggunakan teknik uji instrumen menggunakan regresi linier berganda dengan aplikasi SPSS versi 25. Hasil pada penelitian ini menunjukkan bahwa Digital Enviroment, Dynamic Managerial Capabilities, Transformational Leadership, Organizational Culture berpengaruh positif terhadap Organizational Performance. Implikasi manajerial dalam penelitian ini adalah diharapkan organisasi dapat menetapkan visi, nilai, dan prioritas bersama yang disepakati semua orang yang ada organisasi dan organizational culture tertentu harus sesuai dibawah kondisi khusus untuk meningktakan produktivitas dan efiensi. Kata Kunci: Digital Enviroment, Dynamic Managerial Capabilities, Transformational Leadership, Organizational Culture, Organizational Performance